Pengabdian Masyarakat dalam Mengurangi Sampah Plastik dengan menggunakan teknik Ecoprint Masyarakat di Desa Sumput Sidoarjo - Budi Prabowo; Ahmad Fahturrozak; Lailatul Fitriyah; Friya Samudatul Aisyah; Imanda Aditya Setyawan (Universitas 45 Surabaya, 2024)
Ecoprint is a fabric dyeing technique using natural materials such as leaves and flowers to create unique patterns and colors. This technique is an environmentally friendly alternative compared to conventional methods that use dangerous chemicals. Apart from producing aesthetic products, ecoprint also reduces waste and energy consumption. This research explores the use of ecoprint in making tote bags, by utilizing waste cassava leaves and papaya leaves. On July 31 and August 4 2024, the Business Plan Socialization Program (SIBAL) in Sumput Village involved PKK cadres and mothers. Activities include explanations, practice, questions and answers, and giving prizes. The results show participants' enthusiasm in learning ecoprint techniques, as well as increased understanding of environmental benefits and business potential. In conclusion, ecoprint is a sustainable solution for environmentally friendly fashion production and supports the principles of sustainability.